Demonic or Divine? Theravāda Buddhist Interpretations of Jesus - Schneider, Mathias (Buddhist Christian studies, 2019)
This article presents a brief overview of Theravāda Buddhist portrayals of Jesus. As will become clear, their views are significantly shaped by their respective historical context. In Asia, the first encounters between Buddhism and Christianity took place under the conditions of European colonial rule and were informed to a large extent by the Buddhist experience of Christian mission. This is particularly true for Sri Lanka, where interpretations that depict Jesus in a predominantly negative light developed. At the other end of the spectrum, we find the interpretation of Jesus as a Buddha by the Thai Buddhist reformer Buddhadāsa Bhikkhu. Such a positive assessment of Jesus may in part be influenced by the fact that Thailand has never directly been under Western colonial rule. With the German-born Buddhist nun Ayya Khema, a Buddhist interpretation of Jesus will be taken into account that originated in the West, where Christianity is not a foreign religion, but an established social, cultural, and spiritual force.